Health related quality of life and associated factors among patients treated for ischemic heart disease in public sector hospital Karachi, Pakistan - Khan, Arshad Nawaz; Sarfraz Masih; Jawaid Akber Sial; Aziz, Tariq; Nadir Jaseem (Journal of the Pakistan Medical Association, 2024)
Objective: To determine the level of health-related quality of life among patients treated for ischemic heart disease in a public-sector tertiary care setting. Method: The analytical cross-sectional study was conducted from July to September 2021 at two tertiary care hospitals in Karachi after approval from the ethics review boards of the National Institute of Cardiovascular Diseases and the Dow University of Health Sciences, and comprised patients of either gender treated for ischemic heart disease after being diagnosed within the preceding year who were coming for follow-up in the outpatient department. Data was collected using the short version of the World Health Organisation quality of life tool. Association of socio-demographic and clinical variables with health-related quality of life was explored. Data was analysed using SPSS 21. Results: Of the 300 patients aged 25-85 years, 212(70.7%) were males and 88(29.3%) were females. The mean total quality of life score was 6.1+/-1.4, while mean general health was 52.6+/-10.5. The lowest score among quality of life subscales was for environmental 44.7+/-15.1, while the highest score was for psychological 60.1+/-10.7 domains. Quality of life was significantly associated with patients’ age, education, comorbidities, marital status, monthly income, body mass index, activities of daily living and smoking status (p<0.05). Conclusion: Ischemic heart disease patients had average health-related quality of life in all domains, but showed low quality of life in the environmental domain. Key Words: Health-related quality of life, Cardiovascular diseases, QOL, Quality of life, Ischemic heart disease, Coronary artery disease.